Metal-phenolic network as precursor complex coating for forward osmosis membrane with enhanced antifouling property - Yan Sun; Xiaoyang Xie; Xiangdong Ma; Qianying Feng; Changhao Xu; Jiaqi Shen; Yuxin Gu; Chuanliang Zhao; JiaoJie He (Water Science and Technology, 2024)
In this study, a multi-functional layer was developed based on the commercially available cellulose triacetate (CTA) forward osmosis (FO) membrane to improve its antifouling property. Tannic acid/ferric ion (TA/Fe3+) complexes were firstly coated as a precursor layer on the membrane surface via self-assembly. Afterwards, the tannic acid/diethylenetriamine (TA/DETA) hydrophilic functional layer was further coated, following Ag/polyvinylpyrrolidone (PVP) anti-bacterial layer was formed in situ through the reducibility of TA to obtain TA/Fe3+-TA/DETA-Ag/PVP-modified membrane. The optimized precursor layer was acquired by adjusting the buffer solution pH to 8, TA/Fe3+ ratio to 4 and the number of self-assembled layers to 5. The permeability testing results illustrated that the functional layer had an insignificant effect on the membrane transport parameters. The TA/Fe3+-TA/DETA-Ag/PVP-modified membrane simultaneously exhibited excellent physical and chemical stability. The coated membrane also demonstrated enhanced anti-bacterial properties, achieving 98.63 and 97.30% inhibition against Staphylococcus aureus and Escherichia coli, respectively. Furthermore, the dynamic fouling experiment showed a 12% higher water flux decrease for the TA/Fe3+-TA/DETA-Ag/PVP CTA membrane compared to the nascent CTA membrane, which proved its excellent antifouling performance. This work provides a feasible strategy to heighten the antifouling property of the CTA FO membrane. HIGHLIGHTS Surface modification of CTA FO through TA/Fe3+ and TA/DETA coating layers and in situ reduction of Ag.; The multi-functional layer had no considerable impact on the mass transport coefficients of the CTA FO membrane.; The antifouling of the modified membrane was remarkably improved for raw municipal wastewater treatment.;